Therapeutic Community: Towards a living of the pedagogy of autonomy - Roberto Krüger, Rolf (Vox Scripturae - Revista Teológica Internacional, 2014)
The therapeutic proposal of Therapeutic Communities point to the reorganization of life that presuppose a relearning of the well being, through living in micro-societies. In these institutions, occurs a meeting of different knowledge in experiential applicability. The institution provides a therapeutic space of living, with adequate infrastructure, therapeutic team and a therapeutic program, however it is the resident who should be the agent of its own recuperation, fitting to the recuperation offerers only to reinforce the motivational matters. In the knowledge, contributions from the pedagogy of autonomy from Paulo Freire are consistent so the teaching-learning relation can lead to effectiveness of what De Leon presents as internalization. For this, it is important to have consciousness that the “therapeutic-program” is, by excellence, an “educative-program” that respects the autonomy of the resident taking him to the compromise with the other. Thus, autonomy does not take to individualism, but on the contrary, it rescues this one and points to a communitarian living.